The Da'wah Approach of Ustadzah Halimah Alaydrus on Instagram - Liza Nuarida Ulfah Br Barus; Cut Syamsidar; Muhammad Azwar; Fauzi Wirahyuda; Ahmad Tamrin Sikumbang (Jurnal Dakwah dan Komunikasi, 2024)
This study aims to analyze the da'wah method of Ustadzah Halimah Alaydrus on Instagram social media, which is a unique phenomenon due to the high public interest in her da'wah, both online and offline, even though she never shows her face and only uses her voice. This uniqueness creates a research gap, namely the lack of in-depth studies on the effectiveness and strategies of da'wah without facial visualization on social media platforms. This study uses a descriptive qualitative approach, with a data collection method through analysis of Ustadzah Halimah's da'wah content on Instagram, and is supported by relevant literature studies. The da'wah method used by Ustadzah Halimah is bil hikmah and mauidzatil hasanah, which means conveying messages wisely and with good advice. The results of the study show how Ustadzah Halimah utilizes social media platforms to convey religious messages effectively without involving visual appearance. Live content presented with a clear voice and a simple but attractive Instagram feed visual design, such as the use of pastel colors and a neat layout, helps maintain the audience's attention. The combination of live preaching content through live videos and aesthetic posts on Instagram feeds allows his preaching messages to be well received by followers. The positive reception of the audience towards this method shows that non-visual preaching can be an effective strategy in spreading religious messages in the digital era.